Solve the following where \(x_1\) and \(y_1\) are parameters/(not variables).

\(y = \frac{-x_1} {2 y_1} \cdot (x - x_1)\)

\(y = \frac{2 y_1}{x_1}(x - x_1/2)\)

Guest May 20, 2019

#1**+1 **

first thing to do is rewrite it so you don't have such confusion

\(x_1=a,~y_1=b\\~\\ y = -\dfrac{a}{2b}(x-a)\\~\\ y = \dfrac{2b}{a}\left(x - \dfrac a 2\right)\)

\(-\dfrac{a}{2b}(x-a)=\dfrac{2b}{a}\left(x-\dfrac a 2\right)\\~\\ -\dfrac{a^2}{4b^2}(x-a) =\left(x-\dfrac a 2\right)\\~\\ \dfrac{a^3}{4b^2}+ \dfrac a 2= x\left(1+\dfrac{a^2}{4b^2}\right)\\~\\ x = a\dfrac{\dfrac{a^2+2b^2}{4b^2}}{\dfrac{4b^2+a^2}{4b^2}}\\~\\ x = a \dfrac{a^2+2b^2}{a^2+4b^2}\)

Now you can substitute back in x_{1} for a and y_{1} for b

Rom May 20, 2019